Wet Chemical Approach for Vanadium Doped Maghemite (Fe2-xVxO3) Nanocrystals - Hasany, S. F.; Nour, A. H.; Sunarti, Abd Rahman (Bentham Science, 2016)
Background: Nanomaterials are widely synthesized by wet chemical routes. Magnetic nanoparticles with size ranging from 2 to 20 nm are of significant importance, resulting in a unique magnetic property of the nanoparticles. Maghemite nanostructures with partially disordered (Fe3+)[Fe5/3⁏1/3]O4 structures, undergo cation-insertion reactions without resorting to a drastic change in the material composition. Tailoring the superparamagnetic properties of nanoparticles by doping with transition metals, such as vanadium could be advantageous, as it would provide control over properties that are important for biological applications, such as magnetization dependent changes in temperature, relaxivity, and hysteresis. Method: We describe the obtention of vanadium doped maghemite (Fe2-xVxO3) from colloidal suspensions of vanadium and iron salts, using a precipitation–annealing method. A single step simpler synthesis scheme has been proposed in this work, with annealing temperature (350 °C), for a short period of time (~ 15 minutes), in order to achieve smaller in size but developed nanocrystals. Results: Superparamagnetic vanadium doped maghemite with particles (~8 nm) size has been synthesized. For the first time, vanadium up to 5 mol% has been doped on maghemite nanocrystals and characterized successfully for the presence of stable V3+. These results open a new era of vanadium applications in industrial Nanosciences; possessing superparamagnetic properties. Conclusion: A wet chemical route to direct the synthesis of vanadium doped γ- Fe2O3 nanocrystals, has been studied. The doping controls the crystallite size by occupying the vacant octahedral spaces available in the cubic system (space group P4332) maghemite crystals. High surface area magnetic particles, with an average size of ~8 nm were obtained.